EVALUASI PEMBELAJARAN BAHASA INDONESIA PADA KELAS XI IPA MADRASAH ALIYAH NEGERI KARANGANYAR TAHUN PELAJARAN 2012/2013 - Subekti, Subekti; Markhamah, Markhamah; Nasucha, Yakub (Jurnal Penelitian Humaniora, 2014)
This study aimed to evaluate the Indonesian language learning in class XI IPA Madrasah Aliyah Negeri Karanganyar, especially related to: (1) Quality of learning of Indonesian in terms of school environment, (2) the quality of learning inputs, namely student motivation, teacher competence, learning programs, and infrastructure, (3) the quality of the learning process, namely: teacherâs roles in the classroom, studentsâroles and learning activities and learning environmnet, and (4) the studentsâ learning outcome. The type of research is evaluation model using a quanlitative and quantitative approaches. Evaluation model used is the model CIPP (context, input, process, product). Data collection is carried out through questionnaires, interviews, observation and documenta tion. The data analysis technique used is the evaluative analysis conducted qualitatively and quantitatively. The results showed as follows: (1) Learning environment is conducive for learning process (stated by 96.4% of students); (2) studentsâmotivation in learning is good (stated by 96.7% of students) although teachers lack in classroom management skills; (3) The teachers role and activities are good (stated by 84.9% of students); studentsâ activities in classroom are goog (stated by 90.6% of students); (4) school environment is condusive for learning (stated by 95.6 % of students); and (5) the academic achievement of students is good (meased through the average score of the second semester of academic year 2012/201).